Distribution of training volume and intensity of elite male and female track and marathon runners - Enoksen, E.; Tjelta, A. R.; Tjelta, L. I. (International Journal of Sports Science and Coaching, 2011)
The aim of this study was to compare training volume and the distribution of training intensity of six of the best long-distance runners in Norway from the last decade.